2018
DOI: 10.4314/njbas.v25i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient supplementation on single cell protein production from watermelon and pineapple peels

Abstract: The fast growing population of the world has led to an increased demand for protein rich food; this exerts great pressure on food and feed industries to produce sufficient quantities of protein to meet the high nutrient requirements of vulnerable populations (children and women). Single cell protein (SCP) has proven to be a sustainable approach since agricultural residues can be used for the production. In the present study, efforts were made to improve the growth support capacity of watermelon and pineapple f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Watermelon, mixture of fruit wastes SF/LSF [89] Watermelon, pineapple SF/LSF [90] Yam peel SF/LSF [91] Apple, orange peel SF/LSF [36] Cucumber peel, orange peel SF/LSF [20] Pineapple waste SF/LSF [11,46,92,93] Papaya waste SF/LSF [94] Apple, papaya, banana SF/LSF [77] Guava peels and cashew bagasse SSF [95] Rind of pomegranate, mango, banana, apple, sweet orange peel SSF [79] Orange peels SSF [96,97] Pichia pinus Mango waste SF/LSF [98]…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Watermelon, mixture of fruit wastes SF/LSF [89] Watermelon, pineapple SF/LSF [90] Yam peel SF/LSF [91] Apple, orange peel SF/LSF [36] Cucumber peel, orange peel SF/LSF [20] Pineapple waste SF/LSF [11,46,92,93] Papaya waste SF/LSF [94] Apple, papaya, banana SF/LSF [77] Guava peels and cashew bagasse SSF [95] Rind of pomegranate, mango, banana, apple, sweet orange peel SSF [79] Orange peels SSF [96,97] Pichia pinus Mango waste SF/LSF [98]…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…The study of A. K Mondal et al, (2012) also reported that the supplemented fruit hydrolysates medium yielded low yeast biomass of Saccharomyces cerevisiae and low protein (17.47%) content than glucosesupplemented fruit hydrolysate medium. The study of Abarshi et al (2017) also involved the effects of nutrient supplementation on SCP production from fruit peels of watermelon and pineapple using Saccharomyces cerevisiae. It revealed that the highest concentrations of crude protein (20g/l) was produced in fruit hydrolysates media supplemented with glucose and nitrogen on the 16 th day of fermentation as compared to the control fruit hydrolysates (5.6 g/l) without nutrient or glucose supplementation.…”
Section: Effect Of Nutrient Supplementation On Fungal Biomass and Pro...mentioning
confidence: 99%
“…In the early fifties, an alternative source of proteins was introduced as single-cell protein due to the lack of availability of enough protein sources 1 . used as beneficial substrates for SCP production 4 . Orange peel wastes are rich sources of cellulose (9.21%), hemicelluloses content (10.5%), and pectin content (42.5%).…”
Section: Introductionmentioning
confidence: 99%